What Knowledge do Slovak Students and Primary Education Teachers Have about the Movements of Celestial Bodies? - Velmovská, Klára (Scientia in educatione, 2020)
Students get the basic knowledge about the universe in science classes in years 3 and 4 and in some geography classes in year 5. In physics classes they get in touch with astronomy; however, only marginally. Using questionnaire we investigated what knowledge of the motion of celestial bodies have selected groups of respondents in Slovakia — we compared these groups and identified the misconceptions connected with this theme. After evaluation and statistical processing of the questionnaire’s results we found out, that primary school and university students have comparable level of knowledge about this topic. Although the level of knowledge of primary education teachers surpasses the level of knowledge of university students, the success rate of this group according to questionnaire with basic questions about the motion of celestial bodies does not exceed 60 %.